Analysis of Spiritual Well Being on the Quality of Life of Patients with Diabetes Mellitus in Tambun Health Center Area - Ika Juita Giyaningtyas; Beatrix Elizabeth (PROMOTOR, 2024)
Diabetes mellitus is a chronic disease that cannot be completely cured which affects Diabetes Quality of Life (DQoL). Spirituality is an element that can affect quality of life, especially in patients with diabetes mellitus. This study aims to analyze spiritual well being on the quality of life of patients with diabetes mellitus. This research is correlational with a cross sectional approach. Respondents in this study amounted to 38 respondents who were taken by accidental sampling technique. The research instruments used were the Spiritual Well Being (SWB) and DQoL questionnaires. The results of this study indicate that there is a relationship between spiritual well being and the quality of life of patients with diabetes mellitus in the Tambun Health Center area. Thus, the higher the spiritual well being value of diabetes mellitus patients, the better the patient's quality of life.